The representation ring of a non-pointed bialgebra - Huaqing Gong; Shilin Yang (AIMS Mathematics)
The aim of this paper is to characterize the representation ring of a non-pointed and noncocommutative bialgebra. First, the isomorphism classes of its indecomposable modules are classified. Then the tensor product of modules is established. Finally, its representation ring is described.